2013
DOI: 10.1177/0022487113496431
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Validity of Measures of Teacher Candidate Programs and Performance

Abstract: Calls for evidence-based reform of teacher preparation programs (TPPs) suggest the question: Do the current indicators of progress and performance used by TPPs predict effectiveness of their graduates when they become teachers? In this study, the indicators of progress and performance used by one program are examined for their ability to predict value-added scores of program graduates. The study finds that rating instruments, including disposition surveys, clinical practice observation ratings, and portfolio a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…Hence, stereotypes about teachers' qualities are often defined in relation to a binary opposite, such as efficient and inefficient, new and old and progressive contra traditionalist (Hanushek, 2002;Henry et al, 2013), for example: '[t]he new [educational] system is ridiculous. Let's go back to the old ways' (Pascoe, 1993, p. 60, in Thomas, 2004).…”
Section: Examples Of Media Images Of Teachers and Educational Researcmentioning
confidence: 99%
“…Hence, stereotypes about teachers' qualities are often defined in relation to a binary opposite, such as efficient and inefficient, new and old and progressive contra traditionalist (Hanushek, 2002;Henry et al, 2013), for example: '[t]he new [educational] system is ridiculous. Let's go back to the old ways' (Pascoe, 1993, p. 60, in Thomas, 2004).…”
Section: Examples Of Media Images Of Teachers and Educational Researcmentioning
confidence: 99%
“…The mean cost of selection methods for the receiving institution or school district was US $104.32 per candidate, with a low of $0 in four studies where existing data such as secondary school or university grades were used for selection (Heinz, 2013;Henry et al, 2013), or where required assessments were used with costs borne by the candidates (e.g., Denner, Norman, & Lin, 2009). The highest costs (e.g., $289.61, $209.13) were calculated for assessment centers requiring multiple assessors (e.g., Bieri & Schuler, 2011) and selection methods that required initial training costs (e.g., $2500 for the TPI in Bingham, 2000) in addition to time required for interviews.…”
Section: Cost Of Selection Methodsmentioning
confidence: 99%
“…As part of this work, CU found that its self-developed candidate portfolio assessment failed to identify the multiple constructs it was designed to assess and was not predictive of graduate outcomes (Henry et al, 2013). This lack of valid assessment data upon which to base program improvement efforts and respond to new accountability pressures drove CU to seek a new portfolio assessment.…”
Section: Tpa Scoring Procedures At Collaborating Universitymentioning
confidence: 99%
“…At least one study suggests that many traditional measures of teacher candidate performance, such as grade point average, licensure exam scores, dispositional ratings, and student teaching ratings, do not meet all these criteria and thus, may be of limited use for evidence-based program improvement (Henry et al, 2013). In recent years, however, many teacher educators have supported the creation and widespread adoption of teacher candidate performance assessmentsdone of which has received widespread attention, the Teacher Performance Assessment (TPA).…”
Section: Introductionmentioning
confidence: 99%